2007
DOI: 10.1017/s0890060407000339
|View full text |Cite
|
Sign up to set email alerts
|

Comparing entropy measures of idea links in design protocols: Linkography entropy measurement and analysis of differently conditioned design sessions

Abstract: 2007). Comparing entropy measures of idea links in design protocols: Linkography entropy measurement and analysis of differently conditioned design sessions. AbstractThis paper explores using Shannon's entropy of information to measure linkographs of 12 design sessions that involved six architects in two different experimental conditions. The aim is to find a quantitative tool to interpret the linkographs. This study examines if the differences in the design processes and the design outcomes can be reflected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Linkography research reported that the most creative and productive works, highly evaluated by the experts, had denser and more integrated structure of Linkographs (Goldschmidt & Tatsa, 2005;Van der Lugt, 2003). Moreover, Linkograph metrics were found to reflect the differences between expert and novice designers (Cai, Do, & Zimring, 2010;Kan, Bilda, & Gero, 2007).…”
Section: Creative Processes During a Collaborative Drawing Task In Tementioning
confidence: 99%
“…Linkography research reported that the most creative and productive works, highly evaluated by the experts, had denser and more integrated structure of Linkographs (Goldschmidt & Tatsa, 2005;Van der Lugt, 2003). Moreover, Linkograph metrics were found to reflect the differences between expert and novice designers (Cai, Do, & Zimring, 2010;Kan, Bilda, & Gero, 2007).…”
Section: Creative Processes During a Collaborative Drawing Task In Tementioning
confidence: 99%
“…Similarly, a quantitative tool was implemented to interpret the linkography using entropy. 20 Kan and Gero 24 also evaluated the entropy of Shannon's information theory as a tool for measuring the creativity of design in a protocol analysis method. In addition, a method was developed for measuring the design process and correlating through assessing the design outcome using a linkography analysis technique in a protocol study.…”
Section: Linkography and The Design Processmentioning
confidence: 99%
“…A small entropy fluctuation reflects the staged concept concentration or new potential concepts. 25,26 Therefore, entropy fluctuation can represent the transition, new, or isolated concept during a design cognition process.…”
Section: H(p I ) Is the Continuous Function Of P I Andmentioning
confidence: 99%